Oxide catalyst with structure of embedding cerium into zinc-iron spinel as well as preparation method and application of oxide catalyst
By embedding cerium into the zinc-iron spinel structure to form a highly active and selective oxide catalyst, the problem of poor catalytic performance of traditional iron-based catalysts in carbon dioxide hydrogenation catalysis is solved, and the effect of efficient preparation of light olefins under mild conditions is achieved.
Patent Information
- Application Number
- CN202510003384.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-01-02
AI Technical Summary
In the hydrogenation of carbon dioxide, existing iron-based catalysts have problems such as insufficient catalytic performance, large reaction particles, and insufficient catalytic activity under mild conditions.
By solidly resolving a variety of different metal components, forming a single-phase stable oxide catalyst with cerium embedded in the zinc-iron spinel structure. The embedding of cerium replaces the position of iron in the lattice and forms cerium dioxide on the surface, promoting the conversion and dissociation of CO2.
Under milder conditions, the oxide catalyst embedded in the zinc-iron spinel structure of cerium shows high activity, selectivity and simple production of CO2 hydrogenation to light olefins, suitable for industrial applications.
Smart Images

Figure CN119680559A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst materials, in particular to an oxide catalyst with a cerium-embedded zinc-iron spinel structure and a preparation method and application thereof. Background Art
[0002] At present, global energy shortage and environmental problems are becoming increasingly serious. Therefore, it is urgent to find a series of clean, sustainable and alternative green energy sources. Carbon dioxide hydrogenation is a clean energy conversion technology that can convert coal, biomass and synthesis gas (a mixture of H2 and CO2) in the atmosphere into high-value hydrocarbon chemicals and liquid oils, such as olefins, gasoline and diesel. However, the synthesis of these products requires catalysts as a medium to regulate the products in a targeted manner.
[0003] Traditional iron-based catalysts are widely used in carbon dioxide hydrogenation catalysis due to their simple production and rich products. However, traditional iron-based catalysts also have a series of problems, such as insufficient catalytic performance and large reaction particles. Through improvements, spinel oxide catalysts have emerged, but ordinary spinel oxides are difficult to catalyze reactions under milder conditions and have the problem of few active sites, and the selectivity of the final olefin products is still unsatisfactory. At present, some modified zinc-iron catalysts have been used for CO2 hydrogenation to synthesize light olefins, but they all have more or less some problems such as harsh reaction conditions and low target products. Therefore, it is very important to develop a catalyst with high activity, high selectivity and reaction under mild conditions in the process of carbon dioxide hydrogenation to light olefins. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a cerium-embedded zinc-iron spinel structure oxide catalyst and its preparation method and application. The present invention improves the catalytic activity of the catalyst by solid-dissolving a plurality of different metal components to form a single-phase stable spinel catalyst. On the one hand, the embedding of cerium replaces the position of iron in the lattice to form a new active site, and on the other hand, cerium dioxide is formed on its surface to promote the conversion and dissociation of CO2, thereby obtaining a catalyst material for CO2 hydrogenation to light olefins with high activity, selectivity and simple production under relatively mild conditions.
[0005] The technical solution adopted by the present invention to solve its technical problem is:
[0006] A method for preparing a cerium-embedded zinc-iron spinel structure oxide catalyst comprises the following steps:
[0007] Step S1, dissolving iron salt, zinc salt and cerium salt in deionized water, slowly adding 28% NH4OH solution and stirring evenly to obtain a mixed solution; subjecting the mixed solution to a hydrothermal reaction; the hydrothermal reaction condition is 120-180°C;
[0008] Step S2, after the hydrothermal reaction is completed, the mixture is cooled to room temperature, the solution after the reaction is collected, centrifuged and washed, and then placed in an oven for drying at a temperature of 60 to 100° C. for 10 to 14 hours to obtain a metal composite material;
[0009] Step S3, loading the dried metal composite material with sodium salt by an impregnation method;
[0010] Step S4, placing in a tubular furnace and calcining under argon conditions, the calcination temperature is 300-500° C., and maintained for 2-5 hours, and after calcination, a finished cerium-embedded zinc-iron spinel structure oxide catalyst is obtained.
[0011] Furthermore, in step S1, the iron salt is one or more of ferric chloride trihydrate, anhydrous ferric chloride, ferric nitrate nonahydrate, ferric sulfate pentahydrate, and ferric acetate tetrahydrate; the zinc salt is one or more of zinc chloride tetrahydrate, zinc nitrate hexahydrate, zinc sulfate heptahydrate, and zinc acetate dihydrate; and the cerium salt is one or more of cerium nitrate hexahydrate, cerium chloride hexahydrate, and the like.
[0012] Furthermore, in step S1, the molar ratio of the iron salt, the zinc salt and the cerium salt is (1.95-1.99):1:(0.01-0.05).
[0013] Furthermore, in step S1, the reaction temperature of the hydrothermal reaction is 180° C., and the reaction time is 24 h.
[0014] Furthermore, in step S2, the drying temperature is 80° C. and maintained for 12 hours.
[0015] Furthermore, in step S3, the loading amount of the sodium salt is 1%.
[0016] Furthermore, in step S4, the calcination temperature is 400° C. and maintained for 3 hours.
[0017] A cerium-embedded zinc-iron spinel structure oxide catalyst is prepared by the preparation method according to any one of claims 1 to 7.
[0018] An application of the above-mentioned cerium-embedded zinc-iron spinel structure oxide catalyst, and application of the cerium-embedded zinc-iron spinel structure oxide catalyst in carbon dioxide hydrogenation catalysis.
[0019] Furthermore, the application is specifically as follows: a cerium-embedded zinc-iron spinel structure oxide catalyst is reduced with H2, loaded into a fixed fluidized bed, a mixed gas composed of CO2 and H2 is introduced, and a hydrogenation reaction is carried out at a temperature of 290°C and a pressure of 2MPa, wherein the molar ratio of CO2 to H2 is 1:3.
[0020] The beneficial effects of the present invention are as follows: the present invention has a reasonable design, a simple preparation method, and has the following advantages:
[0021] (1) The zinc-iron spinel oxide catalyst prepared by the present invention is prepared by a precipitation-hydrothermal method, which is simple to produce and the raw materials are cheap, and is conducive to industrial production. At the same time, the physical and chemical properties of the catalyst can be regulated by adjusting the content of embedded cerium. On the one hand, the embedding of cerium can greatly improve the adsorption and activation ability of the catalytic material for the reaction gas, thereby accelerating the reaction process. On the other hand, the abundant active sites improve the carburizing ability of the catalytic material, improve the O / P ratio, and facilitate the synthesis of the target product.
[0022] (2) The cerium-embedded zinc-iron spinel structure oxide catalyst prepared by the present invention shows excellent catalytic activity under relatively mild conditions, and the CO2 conversion rate, olefin selectivity and space-time yield are all excellent, which can provide broad prospects for subsequent industrial applications and olefin production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 is an X-ray powder diffraction (XRD) diagram of the catalyst after the reaction in Examples 1 to 3 and Comparative Examples 1 to 2;
[0025] Figure 2 is the X-ray powder diffraction (XRD) pattern of the fresh catalyst in Examples 1 to 3 and Comparative Examples 1 to 2;
[0026] Figure 3 is the morphology (TEM) of the fresh catalyst in Example 1;
[0027] Figure 4 It is the N2 adsorption-desorption isotherm of the catalysts in Examples 1 to 3 and Comparative Examples 1 to 2;
[0028] Figure 5 It is a graph showing the change in CO2 conversion rate of the catalysts in Examples 1 to 3 and Comparative Examples 1 to 2 over time. DETAILED DESCRIPTION
[0029] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] A method for preparing a cerium-embedded zinc-iron spinel structure oxide catalyst comprises the following steps:
[0033] A. Dissolve three different metal salt solutions in deionized water, stir for 10 minutes, then slowly add 28% NH4OH solution, and continue stirring for 1 hour to obtain a precipitated brown solution;
[0034] B. Place the above metal precursor solution into a reaction kettle, heat it to 120-180°C and keep it for 24 hours;
[0035] C. After the reaction is completed, wait for the reactor to cool completely, wash the solution three times with deionized water and anhydrous ethanol by centrifugation, collect the sample after removing the surface solvent and put it into a culture dish;
[0036] D. Place the sample in the culture dish in an oven and dry it at 60-80°C for 10-14 hours;
[0037] E. Take the sample out of the reaction dish, add 200 ml of deionized water and stir, then drop the NaNO3 aqueous solution into it;
[0038] F. After the step is completed, the sample is placed in an oven for drying at 80°C for 12 hours;
[0039] G. Place the mixture in a tubular furnace into which argon gas is introduced and calcined at a temperature of 300-500° C., maintained for 2-5 hours, at a rate of 5° C. / min, to finally obtain a finished product of cerium-embedded zinc-iron spinel.
[0040] Furthermore, the molar ratio of the iron salt, the zinc salt and the cerium salt is 1.95-1.99:1:0.01-0.05.
[0041] The invention provides an oxide catalyst with a cerium-embedded zinc-iron spinel structure, which is prepared by the above method.
[0042] The invention provides an application of a cerium-embedded zinc-iron spinel structure oxide catalyst in chemical catalysis, specifically for catalyzing carbon dioxide and hydrogen to produce high-value chemicals, such as light olefins, under relatively mild conditions.
[0043] The specific application is: used as a catalyst in the carbon dioxide hydrogenation reaction, first reduced for 18 hours at a temperature of 400°C, a pressure of 0.4MPa, and a space velocity of 2500ml / (g*h). After the reduction is completed, the catalyst is loaded into the reactor, and a CO2 / H2 mixed gas with a molar ratio of 1:3 is introduced, and hydrogenation is carried out to prepare olefins at a temperature of 290°C, a pressure of 2MPa, and a space velocity of 2500ml / (g*h). The reaction time is 70 hours.
[0044] Example 1
[0045] A method for preparing a cerium-embedded zinc-iron spinel structure oxide catalyst comprises the following steps:
[0046] A. Dissolve Fe(NO3)3·9H2O (8.03 g), Ce(NO3)3·6H2O (0.04 g), and Zn(NO3)2·6H2O (2.97 g) in 60 ml of deionized water (wherein the molar ratio of Fe:Zn:Ce is 1.99:1:0.01); after stirring for 10 minutes, slowly add 9 ml of 28% NH4OH solution and continue stirring for 1 hour;
[0047] B. Place the above metal precursor solution into a reaction kettle and keep it at 180°C for 24 hours;
[0048] C. After the reaction is completed, wait for the reactor to cool completely, centrifuge and wash the solution three times with deionized water and anhydrous ethanol, collect the sample after removing the surface solvent and put it into a culture dish;
[0049] D. Place the sample in the culture dish in an oven and dry it at 100°C for 12 hours;
[0050] E. Take out the sample from the reaction dish, take out 1.8g, add 200ml deionized water and stir, then drop 0.07g NaNO3;
[0051] After steps F and E, the samples were placed in an oven for drying at 100°C for 12 h.
[0052] G. Place the mixture in a tubular furnace with argon gas and calcine it at 400°C for 4 hours at a rate of 5°C / min. Finally, the catalyst material Ce1ZFO is obtained.
[0053] Experimental operation steps of the catalytic evaluation system: First, weigh a certain amount of catalyst material and quartz sand and mix them evenly. Then, disassemble the reaction tube in the high-pressure catalytic evaluation system, put a small amount of quartz wool and quartz sand in it from top to bottom, put the catalyst in after the height of the quartz sand reaches half of the height, and then put the quartz sand in until the top of the reaction tube, and finally fill a small amount of quartz sand on the top. Tighten the screws of each part and reconnect it to the high-pressure catalytic evaluation system. Make sure that the entire system is leak-proof. First, the above-mentioned catalyst is reduced by hydrogen, specifically: first reduced by H2, the reduction conditions are 0.4MPa pressure, temperature 400℃, space velocity 2500ml / (g*h), after 18h, and used for subsequent catalytic reactions after reduction. After the reduction is completed, the catalyst is loaded into the reactor, and a CO2 / H2 mixed gas with a molar ratio of 1:3 is introduced. Hydrogenation to prepare olefins is carried out under the conditions of temperature 290℃, pressure 2MPa, and space velocity 2500ml / (g*h), and the reaction time is 70h.
[0054] The average data within 70 hours was calculated and the CO2 conversion rate of the catalyst was 38.1%, the CH4 selectivity was 16.7%, and the C2 = -C4 = The selectivity is 46.5%, C5 + The selectivity is 28.6%.
[0055] Example 2
[0056] The difference from Example 1 is that step A in this example is: A. Fe(NO3)3·9H2O (7.95 g), Ce(NO3)3·6H2O (0.12 g), and Zn(NO3)2·6H2O (2.97 g) are dissolved in 60 ml of deionized water (wherein the molar ratio of Fe:Zn:Ce is 1.97:1:0.3); after stirring for 10 minutes, 9 ml of 28% NH4OH solution is slowly added, and stirring is continued for 1 hour.
[0057] In this embodiment, the catalyst material Ce3ZFO is finally obtained.
[0058] The catalytic reaction process was the same as in Example 1. The average data within 70 hours was calculated to obtain a CO2 conversion rate of 32.8%, a CH4 selectivity of 23.5%, and a C2 = -C4 = The selectivity is 40.8%, C5 + The selectivity is 26%.
[0059] Example 3
[0060] The difference from Example 1 is that step A in this example is: A. Fe(NO3)3·9H2O (7.87 g), Ce(NO3)3·6H2O (0.2 g), and Zn(NO3)2·6H2O (2.97 g) are dissolved in 60 ml of deionized water (wherein the molar ratio of Fe:Zn:Ce is 1.95:1:0.5); after stirring for 10 minutes, 9 ml of 28% NH4OH solution is slowly added and stirring is continued for 1 hour.
[0061] In this embodiment, the catalyst material Ce5ZFO is finally obtained.
[0062] The catalytic reaction process was the same as in Example 1. The average data within 70 hours was calculated to obtain a CO2 conversion rate of 31.6%, a CH4 selectivity of 26.9%, and a C2 = -C4 = The selectivity is 39%, C5 + The selectivity is 24.2%.
[0063] Comparative Example 1
[0064] The difference from Example 1 is that the metal element Ce is reduced in step A of this comparative example, specifically:
[0065] A. Dissolve Fe(NO3)3·9H2O (8.08 g) and Zn(NO3)2·6H2O (2.96 g) in 60 ml of deionized water (wherein the molar ratio of Fe:Zn is 2:1); after stirring for 10 minutes, slowly add 9 ml of 28% NH4OH solution and continue stirring for 1 hour.
[0066] The catalyst material ZnFe2O4 was finally obtained in this comparative example.
[0067] The catalytic reaction process was the same as in Example 1. The average data within 70 hours was calculated to obtain a CO2 conversion rate of 29.7%, a CH4 selectivity of 23.9%, and a C2 = -C4 = The selectivity is 39.8%, C5 + The selectivity is 26.9%.
[0068] Comparative Example 2
[0069] The difference from Example 1 is that in step A of this comparative example, Ce(NO3)3·6H2O is impregnated together with NaNO3 in step E, specifically:
[0070] A. Fe(NO3)3·9H2O (8.08 g), Zn(NO3)2·6H2O (2.97 g), and Ce(NO3)3·6H2O (0.04 g) were dissolved in 60 ml of deionized water (wherein the molar ratio of Fe:Zn:Ce was 2:1:0.01); after stirring for 10 minutes, 9 ml of 28% NH4OH solution was slowly added and stirring was continued for 1 hour.
[0071] The catalyst material Ce1@ZFO was finally obtained in this comparative example.
[0072] The catalytic reaction process was the same as in Example 1. The average data within 70 hours was calculated to obtain a CO2 conversion rate of 28.6%, a CH4 selectivity of 24.9%, and a C2 = -C4 = The selectivity is 39.4%, C5 + The selectivity is 14.4%.
[0073] The catalytic performance of the catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was tested. The test results are shown in Table 1.
[0074] Table 1 Catalytic performance of Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3
[0075]
[0076] Table 1 shows the average performance of the catalysts at different calcination temperatures over a 70-hour period. The CO2 conversion rate of Ce1ZFO of the present invention reaches 38.1%, the carbon monoxide selectivity is only 11.8%, the CH4 selectivity is 16.7%, and the C2 = -C4 = The selectivity is 46.5%.
[0077] By comparing Example 1, Example 2 and Example 3, it can be seen that with the increase of embedded Ce content, the conversion rate of CO2 decreased from 38.1% to 31.6%, the selectivity of CH4 increased from 16.7% to 26.9%, and the selectivity of C2 = -C4 = The results show that the increase of Ce content is not conducive to the conversion of CO2, thereby inhibiting CC coupling and forming a large amount of methane. Figure 1 , Table 1, Examples 1 to 3 show that compared with ZFO, the embedding of a small amount of Ce is more conducive to the formation of Fe5C2, thereby improving the carburizing ability and promoting the CC coupling to synthesize light olefins. Figure 2As shown in the figure, the main phase of these five samples is ZnFe2O4, and no other impurities are found, indicating that the embedded Ce is well integrated into ZnFe2O4, which is conducive to maintaining the stability of the crystal. By observing the TEM image of Ce1ZFO ( Figure 3 ) shows that Ce1ZFO is composed of uniformly dispersed small particles with a particle size between 11 and 14 nm, which indicates that it has abundant active sites and catalytic activity. In addition, Figure 4 , the embedding of Ce did not affect the stable structure of the single-phase spinel, which still exhibited a mesoporous structure and promoted the adsorption of gas. Through performance data analysis, it was found that regulating the Ce content is crucial for the hydrogenation of carbon dioxide to produce light olefins. Among them, a small amount of Ce can greatly improve the yield of olefins. With the addition of 1% Ce, there is a significant difference between the Ce1ZFO in Example 1 and the Ce1@ZFO in Comparative Example 2. The CO2 conversion rate dropped sharply from 38.1% to 28.6%, and its O / P also dropped from 5.6 to 4.4. Catalytic stability is the key to the hydrogenation of carbon dioxide to produce light olefins, such as Figure 5 As shown in the figure, all five catalysts reacted continuously for 70 h without showing a significant downward trend, indicating that they have high thermal stability and resistance to deactivation. Combining the above advantages, Ce1ZFO has the best catalytic activity and excellent olefin selectivity.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a cerium-embedded zinc-iron spinel structure oxide catalyst, characterized in that: The specific steps include: Step S1, dissolving iron salt, zinc salt and cerium salt in deionized water, slowly adding 28% NH4OH solution and stirring evenly to obtain a mixed solution; subjecting the mixed solution to a hydrothermal reaction; the hydrothermal reaction condition is 120-180°C; Step S2, after the hydrothermal reaction is completed, the mixture is cooled to room temperature, the solution after the reaction is collected, centrifuged and washed, and then placed in an oven for drying at a temperature of 60 to 100° C. for 10 to 14 hours to obtain a metal composite material; Step S3, loading the dried metal composite material with sodium salt by an impregnation method; Step S4, placing in a tubular furnace and calcining under argon conditions, the calcination temperature is 300-500° C., and maintained for 2-5 hours, and after calcination, a finished cerium-embedded zinc-iron spinel structure oxide catalyst is obtained.
2. The method for preparing a cerium-embedded zinc-iron spinel structure oxide catalyst according to claim 1, characterized in that: In step S1, the iron salt is one or more of ferric chloride trihydrate, anhydrous ferric chloride, ferric nitrate nonahydrate, ferric sulfate pentahydrate, and ferric acetate tetrahydrate; the zinc salt is one or more of zinc chloride tetrahydrate, zinc nitrate hexahydrate, zinc sulfate heptahydrate, and zinc acetate dihydrate; and the cerium salt is one or more of cerium nitrate hexahydrate and cerium chloride hexahydrate.
3. The method for preparing a cerium-embedded zinc-iron spinel structured oxide catalyst according to claim 1, characterized in that: In the step S1, the molar ratio of the iron salt, the zinc salt and the cerium salt is (1.95-1.99):1:(0.01-0.05).
4. The method for preparing a cerium-embedded zinc-iron spinel structure oxide catalyst according to claim 1, characterized in that: In step S1, the reaction temperature of the hydrothermal reaction is 180° C. and the reaction time is 24 hours.
5. The method for preparing a cerium-embedded zinc-iron spinel structured oxide catalyst according to claim 1, characterized in that: In step S2, the drying temperature is 80° C. and maintained for 12 hours.
6. The method for preparing a cerium-embedded zinc-iron spinel structure oxide catalyst according to claim 1, characterized in that: In step S3, the loading amount of the sodium salt is 1%.
7. The method for preparing a cerium-embedded zinc-iron spinel structure oxide catalyst according to claim 1, characterized in that: In the step S4, the calcination temperature is 400° C. and maintained for 3 hours.
8. A cerium-embedded zinc-iron spinel structure oxide catalyst, characterized in that: The cerium-embedded zinc-iron spinel structure oxide catalyst is prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the cerium embedded zinc-iron spinel structure oxide catalyst as claimed in claim 8, characterized in that: The invention discloses an application of the oxide catalyst with cerium embedded in zinc-iron spinel structure in carbon dioxide hydrogenation catalysis.
10. The use of a cerium-embedded zinc-iron spinel structure oxide catalyst according to claim 9, characterized in that: The application is specifically as follows: a cerium-embedded zinc-iron spinel structure oxide catalyst is reduced with H2, then loaded into a fixed fluidized bed, a mixed gas composed of CO2 and H2 is introduced, and a hydrogenation reaction is carried out at a temperature of 290°C and a pressure of 2MPa, wherein the molar ratio of CO2 to H2 is 1:3.
Citation Information
Patent Citations
Catalyst used for producing butadiene through butene oxidative dehydrogenation, and application method thereof
CN105582960A
Loaded type iron-nickel phosphide catalyst material and application thereof
CN105727957A
Preparation method, product and application of catalyst
CN119114086A
Methods and systems for supplying hydrogen to a hydrocatalytic reaction
US20150080621A1
Catalyst for oxidative dehydrogenation and method of preparing the same
US20180333702A1